PENGARUH FRAUD PENTAGON TERHADAP KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAAN INFRASTRUKTUR YANGTERDAFTAR DI BURSA EFEK INDONESIATAHUN 2014 – 2016 - Fitri Damayani; Tertiarto Wahyudi; Emylia Yuniartie (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2017)
The purpose of this research is to examine empirically the influence of fraud pentagon on financial statement fraud. Independent variables that are used in this research are financial stability, financial target, external pressure, managerial ownership, ineffective monitoring, nature of industry, change in auditor, change in directors, and frequent number of CEO’s picture. While dependent variable is financial statement fraud.Population on this research areinfrastructure companies that listed in Indonesian Stock Exhange (IDX) during 2014-2016. By using purposive sampling method, there are 81 samples. The statistical method is multiple linier regression analysis, with hypotheses testing of statistic t-tests, statistic F-tests, and coefficient of determination.The result of this research shows that nature of industry has significant influence onfinancial statement fraud. Whereasthe other independent variables have no influence on financial statement fraud. Simultaneous test result shows that independent variables simultaneously have influence on financial statement fraud.